A REVIEW OF RESEARCH IN MOBILE ASSISTED COLLABORATIVE LANGUAGE LEARNING - Lem, Ngo Cong (VNU Journal of Foreign Studies, 2018)
The article reviewed a selection of research in the field of foreign language teaching into mobile assisted collaborative language learning (Collaborative MALL) – the practice of applying mobile technologies, e.g., applications on mobile phones and laptops, in language teaching context. This review aimed to examine: (1) popular theoretical frameworks previous collaborative MALL research was based upon; (2) merits of applying collaborative MALL in language classroom; (3) strengths and shortcomings of previous studies’ research design and (4) implications for future research as well as for language teaching practice. The findings indicated that three common pedagogical approaches in collaborative MALL studies were game-based, task-based and seamless learning. The confirmed educational affordances of collaborative MALL systems involved facilitating language learners’ collaborative learning process, personalizing learning experience, improving linguistic achievement and enhancing learning motivation/autonomy. Previous research was additionally found to have strong theoretical frameworks, well-designed mobile applications, and examination of both learners’ linguistic improvement and their attitudes towards the technology implementation. However, several methodological weaknesses in previous studies were also identified, e.g., lacking control group in experimental design, insufficient information about the language test format and unclear grading process. Further research with more rigorous research design is warranted to explore the efficacy of collaborative MALL in augmenting learners’ linguistic accomplishments with new mobile applications and in different educational contexts.